Translating across Sensory and Linguistic Borders Intersemiotic Journeys between Media - Campbell, Madeleine; Vidal, Ricarda (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book analyses intersemiotic translation, where the translator works across sign systems and cultural boundaries. Challenging Roman Jakobson's seminal definitions, it examines how a poem may be expressed as dance, a short story as an olfactory experience, or a film as a painting. This emergent process opens up a myriad of synaesthetic possibilities for both translator and target audience to experience form and sense beyond the limitations of words. The editors draw together theoretical and creative contributions from translators, artists, performers, academics and curators who have explored intersemiotic translation in their practice. The contributions offer a practitioner's perspective on this rapidly evolving, interdisciplinary field which spans semiotics, cognitive poetics, psychoanalysis and transformative learning theory. The book underlines the intermedial and multimodal nature of perception and expression, where semiotic boundaries are considered fluid and heuristic rather than ontological. It will be of particular interest to practitioners, scholars and students of modern foreign languages, linguistics, literary and cultural studies, interdisciplinary humanities, visual arts, theatre and the performing arts. Madeleine Campbell is an associate tutor at the University of Edinburgh, UK, and a freelance writer, researcher and translator. She researches intersemiotic translation as practice, and she is also Secretary of Cultural Literacy in Europe, leading its special interest group on Intersemiotic Translation. Ricarda Vidal is a teaching fellow, translator and curator based at King's College London, UK. As curator of Translation Games and Talking Transformations, she explores intersemiotic translation as practice-based research and for public engagement.